The Analysis of Text Printed in Advertisement - Enni Erawati Saragih; Aisyah Noer Nasution (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2015)
The most important component of a language is the functional component, namely meaning creation. Advertisement is a product of marketing process where its process of communication is built interestingly and therefore it is also very interesting to observe the use of language in it. This study focuses on identifying gender ideology and image construction in printed advertisement. The method used is descriptive qualitative. The result shows that every text has a character and its own way in delivering the image of gender, and based on the text analysis, two categories of ideology which core the image of gender are finally revealed; they are sexist and women and men degrees.